2020
DOI: 10.32098/mltj.01.2020.01
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Distal Triceps Brachii Tendon Ruptures. A Systematic Review of Surgical Procedures and Outcomes

Abstract: Background. Chronic and neglected ruptures of distal triceps brachii tendon (TBT), for different reasons, are rarer than acute ruptures. We aimed to review the literature about their surgical treatment and outcome to better understand how to address this kind of rare tendon injuries. Sources of data. Published articles in English in PubMed, Scopus and Google Scholar up to December 2019 about chronic ruptures of distal TBT. Twenty-one papers were included following the Preferred Reporting Items for Systematic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Surgical treatment of chronic QTRs can be challenging because of the large defect and/or tissue degeneration in the substance of the tendon (Table 4). While ruptures of other tendons (Table 5), such as the flexor digitorum profundus and superficialis tendons, require swift intervention because of the prompt retraction of the tendon stumps, in extensor tendons, such as the triceps brachii and quadriceps tendon, retraction is slower, and usually can be treated acutely with direct repair [27]. Recently, a systematic review about chronic QTRs suggested that the timing of surgical intervention plays a crucial role in the functional outcomes, setting the cutoff for early treatment at 2-3 weeks from the injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of chronic QTRs can be challenging because of the large defect and/or tissue degeneration in the substance of the tendon (Table 4). While ruptures of other tendons (Table 5), such as the flexor digitorum profundus and superficialis tendons, require swift intervention because of the prompt retraction of the tendon stumps, in extensor tendons, such as the triceps brachii and quadriceps tendon, retraction is slower, and usually can be treated acutely with direct repair [27]. Recently, a systematic review about chronic QTRs suggested that the timing of surgical intervention plays a crucial role in the functional outcomes, setting the cutoff for early treatment at 2-3 weeks from the injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences studied the timing of intervention after chronic QTRs and set the cut off for early treatment at 2-3 weeks from the injury (19). Indeed, tears of extensor tendons rupture can undergo surgery at later stage than tears of other tendons, such as flexor digitorum profundus and superficialis tendons, as their retraction is not so pronounced (20,21). There are several techniques for repairing a complete quadriceps tendon tear, depending on the location of the tear and the choice of augmentation.…”
Section: Treatment Of Quadriceps Tendon Rupturesmentioning
confidence: 99%